Tween‐85 Surfactant‐Assisted Fabrication of Silver Monoliths for Catalytic Reduction of Methyl Orange and Caffeine Sensing. Issue 16 (24th April 2023) - Nema, Ankita; Bano, Mustri; Rai, Mansi; Shrivastava, Kavya; Dangi, Sambhavna S.; Khan, Farid
Abstract: An elegant method (modified sol‐gel method) was developed to fabricate porous silver (Ag) monoliths using Tween‐85 (T‐85) as a reducing agent with and without dextran (Dex) and TiO2 nanoparticles (TiO2 NPs) for heterogeneous catalysis for the reduction of methyl orange (MO) using sodium borohydride (NaBH4 ), as reducing agent and also sensor against caffeine. Ag/Tween‐85/Dextran/TiO2 NPs (Ag/T‐85/Dex/TiO2 NPs) catalyst was characterized by thermogravimetric analysis (TGA), X‐ray photoelectron spectroscopy (XPS), X‐ray diffraction (XRD), UV‐Vis spectroscopy, transmission electron microscopy (TEM), scanning electron microscopy (SEM), Brunauer‐Emmett‐Teller (BET) adsorption isotherm technique, and Fourier transform infrared (FTIR) analysis. Porous Ag/T‐85/Dex/TiO2 NPs monolith degraded toxic dye methyl orange just in 25 seconds (s) which is the minimum time reported. Cyclic voltammetry (CV) using modified carbon paste electrode (CPE) together with Ag/AgCl as reference and pt as counter electrodes with 0.1 m H2 SO4 as supporting electrolyte were used. Ag/T‐85/Dex/TiO2 NPs−CPE acts as a sensor against caffeine with a limit of detection (LOD) and limit of quantization (LOQ) 0.654 ng mL −1 and 0.876 ng mL −1 respectively and sensitivity is 0.236 μA/mm /cm 2 . Abstract : A modified sol‐gel method for producing Ag/T‐85/Dex/TiO2 NPs catalyst, the results showed that the porous Ag/T‐85/Dex/TiO2 NPs monolith can efficiently degrade toxic dye methyl orange in a record time of 25 s. The cyclic voltammetry (CV) using a modified carbon paste electrode (CPE) to detect caffeine, with a limit of detection (LOD) and limit of quantization (LOQ) were 0.654 ng/mL and 0.876 ng/mL, respectively. The sensitivity of Ag/T‐85/Dex/TiO2 NPs‐CPE was found to be 0.236 μA/mm /cm 2 .